Studi Kasus: Penerapan Pursed Lip Breathing dan Posisi Semi Fowler terhadap Peningkatan Saturasi Oksigen pada Pasien Tuberkulosis Paru (TB Paru) - Wina Anisa; Muadi Muadi; Dewi Erna Marisa (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2026)
Background: Pulmonary tuberculosis is a contagious infectious disease caused by Mycobacterium tuberculosis. Patients with pulmonary tuberculosis frequently experience respiratory problems, such as dyspnea and decreased oxygen saturation, due to impaired gas exchange in the lungs. Objective: This study aimed to determine the effectiveness of the implementation of pursed lips breathing and the semi-Fowler position in improving oxygen saturation among patients with pulmonary tuberculosis in the Emergency Department. Methods: This study employed a descriptive case study design using a nursing care approach for pulmonary tuberculosis patients experiencing ineffective breathing patterns. The intervention consisted of pursed lips breathing exercises and positioning patients in the semi-Fowler position throughout the nursing care process. Results: The findings demonstrated an increase in oxygen saturation from 93% and 94% to 96% and 97%, respectively. In addition, respiratory rate decreased from 28 breaths per minute to 24 breaths per minute, accompanied by improvements in the patients’ breathing patterns following the nursing interventions. Conclusion: The implementation of pursed lips breathing and the semi-Fowler position was effective in improving oxygen saturation among patients with pulmonary tuberculosis in the Emergency Department.